Surgical Treatment of Synchronous Gastric and Esophageal Carcinoma: Case Report and Review of Literature - Xie, Songping; Huang, Jie; Kang, Ganjun; Fan, Guohua; Wang, Wei (The Thoracic and Cardiovascular Surgeon Reports, 2013)
A 65-year-old man was admitted to our hospital because of advanced esophageal squamous cell carcinoma located on the left posterior wall of the lower thoracic esophagus and gastric adenocarcinoma in the antrum. Esophagectomy and distal gastrectomy with two-field lymph node dissection (mediastinum and abdomen) were performed via a left-sided abdominothoracic incision. The remnant gastric was pulled up successfully with the blood supply maintained by the left gastric vessel. He was discharged on the 13th postoperative day without any complications.
Keywords: esophageal cancer; gastric cancer; synchronous; surgery